Studies on mechanical properties of 3 wt% of 40 and 90 µm size B4C particulates reinforced A356 alloy composites. (2022) - Ali, Zeeshan; Muthuraman, V.; Rathnakumar, P.; Gurusamy, P.; Nagaral, Madeva
Abstract: In the present study the A356 alloy composites containing 3 wt% of B4C (40 & 90 µm) particulates were made for the examination. The microstructure of the composite was dissected by checking electron microscopy; micrographs were taken to perceive the proximity of B4C particulates in the matrix. Further, mechanical conduct of as cast A356 combination composite 3 wt% of B4C composites (40 & 90 µm) was inspected. Mechanical properties like hardness, UTS, yield quality were evaluated by ASTM scales. Microstructural investigation exposed the uniform scattering of particles in the A356 composite. From the examination, it was found that hardness, UTS and YS of composite was extended because of essence of B4C particles in the composite.